Length-weight relationship and condition factor of three geographically isolated populations of Hilsa Shad, Tenualosa ilisha (Hamilton, 1822) - Borah, Simanku; G, Vaisakh; Jaiswar, A K; Bhattacharjya, B K; Sahoo, A K; Deshmukhe, G; Raman, R K; Das, B K (Journal of the Inland Fisheries Society of India, 2020)
A study was carried out to analyse and compare population parameters of Hilsa shad, Tenualosa ilisha from three geographically isolated populations residing in three different tropical aquatic ecosystems of India. Monthly sampling was carried from September 2017 to February 2019 and 671 Hilsa specimens were collected in total from Brahmaputra river (n=88), Narmada estuary (n=326) and Ukai reservoir (n=257). Length-weight relationship study showed b value of 2.959, 3.093 and 3.129 for Brahmaputra, Narmada and Ukai respectively. Value of condition factor (K) ranged from 0.8813-0.9908 and that of relative condition factor (Kn) ranged from 1.0016-1.0099 with lowest values obtained from Ukai reservoir in both cases. Key words : Length-weight relationship, Tenualosa ilisha, Brahmaputra river, Narmada estuary, Ukai reservoir